Exploring kindergarten teachers' views and roles regarding children's outdoor play environments in Oman. Issue 1 (2nd January 2016) - Ihmeideh, Fathi M.; Al-Qaryouti, Ibrahim A.
Abstract : The purpose of this study was to explore kindergarten teachers' views and roles regarding outdoor play environments in Omani kindergartens. Thirty kindergarten teachers from 15 private kindergartens were observed and interviewed. The results indicated that teachers recognize the importance of outdoor play in children's development and learning. Although teachers are satisfied with the safety conditions of the outdoor play environments, they feel they need to know more about how to maintain safety criteria in this environment. Teachers most frequently took on the role of supervising and guiding children's behaviour or setting up materials for play, whereas providing verbal comments and participating in play were less common. Omani outdoor play environments were found to face specific difficulties, such as the hot climate, a shortage of materials and equipment, a lack of natural surroundings and the short length of time spent outdoors. The article concludes with policy implications and pedagogical recommendations.